Intelligent approaches to organizing remote quality control of storage of grain products - Diachenko, Vladyslav; Liashenko, Oleksii; Mikhal, Oleg; Umanets, Mariia (Національний технічний університет "Харківський політехнічний інститут", 2021)
Cereals are an essential part of the diet of Homo sapiens. Since late Neolithic times, with the transition to sedentary farming, working with grain (growing, storing, processing, cooking food) has become a traditional type of professional human activity. As part of the accumulated historical experience, numerous technological processes have been developed and optimized for this type of activity. The relevant technologies evolved in close correlation with the changing conditions of life, literally under the pressure of Darwinian natural selection, because they were directly related to the survival of the Homo sapiens. Further development of grain-processing technologies remains invariably urgent today, as evidenced by the report [1] presented by the UN on the state of food security and nutrition in the world - with horrifying figures depicting the need and misery of the wide masses of the population of the planet. An important component of grain processing is the technology associated with the storage of grain products. Part of the stored grain products is used as seed stock for a new cycle of grain sales, the other - a significant part - for processing into food products. At the same time, new developed (optimized, improved) grain storage technologies must be safe, low-cost, maximally compatible with previously developed (available) equipment, and scalable to large volumes of stored material. Of course, the technology must ensure proper efficiency, an indicator of which should be a reduction in the percentage of grain product losses. In this regard, management methods used in the technological processes of grain products storage are substantially important, as well as methods of control over the current state of grain products for the correct organization of the technological processes. In particular, methods using elements of artificial intelligence are of high interest. Among them, neural networks are promising, especially those capable of learning "without a teacher" - Kohonen Maps (KK). Modified KK algorithm [2] implements reduced learning time[3], which is relevant in the implementation of adaptive procedures for processing the results of measurements of controlled parameters. The purpose of this paper is to consider the principles of using modified Kohonen maps to classify situations with applicability to remote quality control of grain products storage.

Зернові - значна частина поживного раціону типу Homo sapiens. З часів пізнього неоліту, з переходом на осілe землеробство, робота із зерном (вирощування, зберігання, переробка, приготування харчових продуктів) стала традиційним видом професійної людської діяльності. В рамках накопиченого історичного досвіду, за цим видом діяльності було розроблено та оптимізовано численні технологічні процеси. Відповідні технології розвивалися у зв'язку зі зміною життєвих потреб, буквально під тиском Дарвінівського природного відбору, оскільки були безпосередньо пов'язані з виживанням виду Homo sapiens. Подальший розвиток технологій зернообробки залишається незмінно актуальним і донині, на підтвердження чого – доповідь [1], подана ООН, про стан продовольчої безпеки та харчування у світі – з жахливими цифрами, що зображують потребу та лиха широких народних мас населення планети. Важливою складовою зернообробки є технології, пов'язані із зберіганням зернопродуктів. Частина зернопродуктів, що зберігаються, використовується як насіннєвий фонд для нового циклу реалізації зернозабезпечення, інша – істотна – для переробки в харчові продукти. При цьому нові технології зернозберігання, що розробляються (оптимізуються, удосконалюються), повинні бути безпечними, маловитратними, максимально сумісними з розробленим раніше обладнанням, масштабованими на великі обсяги матеріалу, що зберігається. Зрозуміло, що технології повинні забезпечувати належну ефективність, показником чого має бути зниження відсотка втрат зернопродукту. У цьому відношенні суттєво важливі методи управління, які застосовуються в рамках технологічних процесів зберігання зернопродуктів, а також методи контролю за поточним станом зернопродуктів для коректної організації роботи технологічних процесів. Цікавими, зокрема, є методи з використанням елементів штучного інтелекту. У тому числі, перспективні нейронні мережі, особливо здатні до навчання "без вчителя" - карти Кохонена (КК). Модифікований алгоритм КК [2] реалізує скорочений час навчання [3], що є актуальним при реалізації адаптивних процедур обробки результатів вимірювань контрольованих параметрів. Мета цієї роботи – розгляд принципів використання модифікованих карт Кохонена для класифікації ситуацій стосовно дистанційного контролю якості зберігання зернових продуктів.
Інтелектуальні підходи до організації видаленого контролю якості зберігання зернових продуктів
Keywords: Kohonen maps; conditions identification system; energy saving; operational deterioration; карти Кохонена; система ідентифікації умов; енергозбереження